Psychological distress and coping strategies among the caretakers of children with transfusion-dependent thalassemia - Othman, Azizah; Abdul Ghani, Mohd Sufian Ardi; Taib, Fahisham; Mohamad, Norsarwany (Frontiers in Pediatrics, 2022)
Introduction Thalassemia is a chronic childhood disease that could result in psychological distress not only to the patients but also to their caretakers. Caretakers utilize different coping strategies to reduce stress and maintain a good quality of life. Objective The study aims to measure the level of psychological distress among caretakers of transfusion-dependent thalassemia patients and identify coping strategies used by them, as well as examine factors related to both outcome measures. Methods Sixty-eight (N = 68) caretakers of children with transfusion-dependent thalassemia agreed to participate in the study when they were approached during their visits to one of three major hospitals in Kelantan, Malaysia, for the children's medical treatment. They completed the Malay validated Depression Anxiety and Stress Scale 21 (DASS 21) and Brief-COPE self-report, in addition to a brief study proforma. Results The majority of the participants reported feeling psychologically well, with no related scores in depression, anxiety, and stress sub-scales. The mean score for anxiety and stress sub-scales were 3.54 (SD = 3.54) and 4.25 (SD = 3.26) respectively. The median score for the depression sub-scale was 2.00 (IQR 4.00). The three mostly utilized coping strategies were religion, acceptance, and positive reframing. Those with depressed and anxious moods were found to engage more in negative coping strategies including substance abuse, denial, and behavioral disengagement. Being female, of younger age, employed, with higher educational level, and income status was found to significantly influence the adoption of positive reframing as a coping strategy. Conclusion Psychological distress such as elevated anxiety and depression was found among a small portion of caretakers who have children with thalassemia whose treatment required blood transfusion. They were noted to apply more maladaptive coping strategies compared to their psychologically well counterparts.